Do Fund Managers of Global Real Estate Funds Exhibit Superior Skill? - Kaushik, Abhay (Journal of Accounting and Finance, 2024)
This study analyzes US-domiciled actively managed global real estate funds (GREMFs) from 1/2010 to 12/2023. The results show superior selectivity and adverse market timing skills of fund managers. On average, GREMFs deliver alpha ranging from 2.52 percent to 2.75 percent per year after controlling for premiums offered by the market, size, value, and momentum effects. The alpha range increases to 4.65 percent annually after including the quadratic term of excess market returns. The results also show that many funds exhibit superior selectivity skills, thus making a case for investors to invest in actively managed GREMFs rather than investing in passive indices. However, the results also indicate that GREMFs are unable to manage beta loadings to their advantage.